Health Effects of Alternate-Day Fasting in Adults: A Systematic Review and Meta-Analysis - Cui, Yuanshan; Cai, Tong; Zhou, Zhongbao; Mu, Yingmei; Lu, Youyi; Gao, Zhenli; Wu, Jitao; Zhang, Yong (Frontiers in Nutrition, 2020)
Background: Alternate-day fasting (ADF) method is becoming more and more popular among adults. This meta-analysis aims to evaluate the effects of ADF on adults. Methods: Randomized controlled trials (RCTs) of ADF were searched using PubMed (1988 to March 2020), EMBASE (1995 to March 2020), and the Cochrane Controlled Trials Register. A systematic review was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-analyses. The datum was calculated by RevMan version 5.3.0. The original references for relating articles were also reviewed. Results: Seven randomized controlled trials involving 269 participants (152 in the ADF group and 117 in the control group) were studied. In this meta-analysis, compared with the control group, the ADF group showed statistically significant reductions in weight (p < 0.00001) and body mass index (p < 0.00001). Besides, the ADF group showed significant differences in terms of total cholesterol (p = 0.001), low-density lipoprotein (p = 0.01), triglycerides (p = 0.02), fat mass (p = 0.002), lean mass (p = 0.002), systolic blood pressure (p = 0.003), diastolic blood pressure (p = 0.007), and total calorie intake (p = 0.007). At the same time, the analysis demonstrated that the ADF group had a same effect compared with control group in aspects of high-density lipoprotein (p = 0.27), homeostasis model assessment-insulin resistance (p = 0.55), and fasting blood sugar (p = 0.09). Conclusions: This meta-analysis suggests that ADF is a viable diet strategy for weight loss, and it has a substantial improvement in risk indicators for diseases in obese or normal people.